Die Theologie in der Vielfalt ihrer Kontexte - Waldenfels, Hans (Zeitschrift für katholische Theologie, 2006)
Given on April 6, 2005 during the dies academicus at the theological faculty of the University of Innsbruck, this paper reflects contemporary frameworks for catholic theology in terms of what is called context and text. The text of theology remains tied to tradition and in particular to the historical figure of Jesus of Nazareth. Any theological reflection of contexts is bound to them.